KAM KOMPLEKTLI SINFLARDA MUSTAQIL ISHLARNI TASHKIL ETISHNING O‘ZIGA XOS JIHATLARI - Yuldosheva, S.A. (SCIENCE and SOCIETY, 2024)
This article describes the factors of the organization of complete classes in low-equipped general education institutions, the advantages and problems of the educational process, the specific aspects of using independent work, individual assignments and handouts in the organization of effective education.